2010
DOI: 10.1002/ana.21843
|View full text |Cite
|
Sign up to set email alerts
|

APOE predicts amyloid‐beta but not tau Alzheimer pathology in cognitively normal aging

Abstract: Objective-To examine interactions of Apolipoprotein E (APOE) genotype with age and with in vivo measures of preclinical Alzheimer's disease (AD) in cognitively normal aging.Methods-Two hundred and 41 cognitively normal individuals, age 45 to 88 years, had cerebral amyloid imaging studies with Pittsburgh Compound-B (PIB). Of the 241 individuals, 168 (70%) also had cerebrospinal fluid (CSF) assays of amyloid-beta 42 (Aβ 42 ), tau, and phosphorylated tau (ptau 181 ). All individuals were genotyped for APOE.Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

84
667
10
7

Year Published

2011
2011
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 778 publications
(768 citation statements)
references
References 77 publications
84
667
10
7
Order By: Relevance
“…One strength of the current study is that participants with a history of antidepressant use did not differ in age, sex, and ApoE status from participants with no antidepressant exposure. Increasing age and ApoE genetic background are the strongest known risk factors for AD and plaque load (33,48); thus it was critical that these parameters were controlled. A limitation of the current study is that, because participants were excluded if their clinical dementia rating (CDR) was greater than zero, antidepressant-treated participants with potential dementia or mild cognitive impairment would have been excluded, producing a selection bias.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One strength of the current study is that participants with a history of antidepressant use did not differ in age, sex, and ApoE status from participants with no antidepressant exposure. Increasing age and ApoE genetic background are the strongest known risk factors for AD and plaque load (33,48); thus it was critical that these parameters were controlled. A limitation of the current study is that, because participants were excluded if their clinical dementia rating (CDR) was greater than zero, antidepressant-treated participants with potential dementia or mild cognitive impairment would have been excluded, producing a selection bias.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 186 cognitively normal participants were recruited into a study for imaging Aβ plaques in late life by PET imaging (32,33). Participants underwent PET Aβ imaging with Pittsburgh Compound B (PIB) and past use of antidepressant drugs was also ascertained (Table 1).…”
Section: Effect Of Antidepressant Drugs On Amyloid Plaque Load In Hummentioning
confidence: 99%
“…This has now been shown to be the case as evidenced by amyloid-imaging studies with Pittsburgh compound B as well as CSF studies using CSF Ab42 in which a decrease has been shown to indicate brain amyloid deposition. Cognitively normal apoE4-positive middle-aged and elderly individuals are much more likely to have brain amyloid (Reiman et al 2009;Morris et al 2010) and low CSF Ab42 (Sunderland et al 2004;Morris et al 2010) than apoE4-negative individuals. Further, apoE2-positive individuals rarely develop fibrillar Ab as defined by a positive amyloidimaging scan (Morris et al 2010).…”
Section: Genetic Clinical and Biomarker Observations On Relationshimentioning
confidence: 99%
“…Cognitively normal apoE4-positive middle-aged and elderly individuals are much more likely to have brain amyloid (Reiman et al 2009;Morris et al 2010) and low CSF Ab42 (Sunderland et al 2004;Morris et al 2010) than apoE4-negative individuals. Further, apoE2-positive individuals rarely develop fibrillar Ab as defined by a positive amyloidimaging scan (Morris et al 2010). Whereas human data supports the idea that apoE isoforms result in differential susceptibilty to Ab aggregation in the brain, animal studies utilizing genetically modified mice that develop Ab deposition and express human apoE isoforms show more directly that human apoE isoforms have a strong effect on the time of onset of Ab aggregation as well as the amount, location, and conformation of Ab in the brain.…”
Section: Genetic Clinical and Biomarker Observations On Relationshimentioning
confidence: 99%
“…The apolipoprotein (APOE) e4 allele is a wellknown susceptibility gene for the development of late-onset AD, occurs in B15% to 20% of the population, and is estimated to account for B40% of AD cases (Devanand et al, 2005;Saunders et al, 1993). The APOE e4 allele has been linked to AD neuropathology (e.g., increases in amyloid b deposition, dysregulation of tau phosphorylation), as well as small vessel arteriolosclerosis and microinfarcts of the deep nuclei in autopsy-confirmed patients with AD, suggesting that the allele also has deleterious effects on cerebral microvascular integrity (Mahley et al, 1996;Morris et al, 2010;Tiraboschi et al, 2004;Yip et al, 2005).…”
Section: Introductionmentioning
confidence: 99%